Synchronous machine fild current calculation taking into account the magnetic satuartion - Ruppert Filho,Ernesto (2002)
A synchronous machine dynamic mathematical model including the saturation effect is presented. The saturation modeling deals with the linkage flux mathematical model and uses the machine d-axis and q-axis magnetizing curves. Results are shown in the form of V curves and comparisons with calculations using non-saturated and saturated reactances are done showing a considerable difference in the excitation current values. Comparisons with experimental data are done.